PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) BERDASARKAN PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 35 TAHUN 2016 DI WILAYAH LOMBOK TIMUR - EVANGELISTA, BEVERLY (GANEC SWARA, 2023)
Most of the land parcels in East Lombok Regency have not been registered, the basis of rights used by land rights holders as proof of land ownership is only in the form of continuous and hereditary. Therefore, it is necessary to formulate a problem, namely how to implement a complete systematic land registration in East Lombok Regency. The research method used is empirical law with three approaches, namely: statutory approach, conceptual approach and sociological approach. In its implementation, the Complete Systematic Land Registration (PTSL) program in Selong District, East Lombok Regency refers to the provisions in PERKABAN Number 1 of 2017 concerning Amendments to PERKABAN Number 35 of 2016 concerning the Acceleration of the Implementation of Complete Systematic Land Registration and PERKABAN Number 37 / Kep-7.1 / I / 2017 concerning Technical Guidelines for Complete Systematic Land Registration where there are several stages in the implementation of the PTSL starting from Preparation (socialization, location determination, manpower planning and formation of an accelerated adjudication committee, training), counseling, juridical data collection, juridical data processing and proof of rights, land inspection, announcement, ratification, issuance of rights determination decrees and rights affirmation/recognition decisions, rights bookkeeping, issuance and submission of certificates, management of warrants/documents and reporting.